Smart Immersion in Marketing : A Study of Technology Convergence and Purchase Intention - Uppal, Arhita; Banerjee, Sonali; Agarwal, Vaishali; Chadha, Priyanka (Indian Journal of Marketing, 2025)
Purpose : The purpose of the research was to examine the role of integrating virtual reality (VR), augmented reality (AR), and artificial intelligence (AI), called immersive technology convergence (ITC), in influencing customer interactions and purchase decision-making in the current marketing environment. Prior studies have focused on them individually, and little has been done on them as a combination in integrated marketing. The proposed research addressed this gap by exploring how the integration of these technologies brought about emotional engagement and assumed credibility to affect the intention to purchase among customers in the phygital marketing setting. Methodology : Both qualitative and quantitative approaches were used in the research. The first section involved the interview of 30 individuals who had previously used AI immersive platforms. Their experiences were analyzed using a structured interview. These interviews revealed that emotional involvement and the credibility of people were influential. In the second section, responses were gathered from 280 individuals selected on the basis of a certain criterion. With the help of statistical tests (EFA, CFA, and SEM), it was learned whether it was a fit or not. These tests examined the relationship between the utilization of new technology, emotions, trust, and purchase decision-making. Findings : The study demonstrated that immersive technologies were very powerful due to their combination when it comes to the level of emotional involvement and the degree of trust. It also revealed that when individuals have an emotional attachment and believe that the information is credible, they tend to desire to purchase. The study indicated that marketing practices through VR, AR, and AI are best applied as part of an integrated system and not as individual instruments. Practical Implications : The results provided marketers with practical information on how to develop immersive promotion strategies. To create attractive and credible experiences in numerous points of contact with customers, companies must integrate VR, AR, and AI. Different interactive advertisements with the input of AI can contribute to the development of trust, the enhancement of emotional bonding, and immersive marketing. Originality : The study contributed to developing research on the topic of immersive marketing, as it defines ITC as a key concept that unifies VR, AR, and AI. Based on a qualitative understanding and statistical modeling, the study provided a framework demonstrating the influence of these immersive technologies in combination on customer engagement and purchase behavior in the phygital marketing environment.